Comprehensive Curriculum for Phantom‐Based Training of Ultrasound‐Guided Intercostal Nerve and Stellate Ganglion Blocks. Issue 10 (7th February 2014) - Brascher, Anne‐Kathrin; Blunk, James Allen; Bauer, Katrin; Feldmann, Robert; Benrath, Justus
Abstract Objective Ultrasound (US)‐guided pain procedures become increasingly important due to their numerous advantages. Solid proficiency is necessary, however, to minimize complications and guarantee adequate performance. To enable beginners to learn the relevant skills in the technique of US‐guided stellate ganglion (SGB) and intercostal nerve block (ICB), a training curriculum was developed and tested using self‐made phantoms. Design The curriculum comprised an introduction to the didactics of US, SGB, and ICB, a demonstration of the techniques by an expert user, as well as hands‐on training of needle guidance using a gel pad and two phantoms. Subjects Three groups of participants with different levels of expertise with US‐guided procedures took part in the curriculum: 12 medical students with no prior experience, 12 anesthesiologists with some experience, and five senior anesthesiologists who already applied these techniques on a regular basis. Methods Participants evaluated the curriculum via questionnaire, and their performance of time until adequate puncture, attempts required for adequate puncture, number of corrections, and unintentional punctures was assessed. Results The medical students significantly increased their speed during both nerve blocks and reduced the number of attempts and corrections necessary to perform adequate ICB. The anesthesiologists with some experience also increased their speed in both blocks. The participants rated the curriculum as good to very good. Conclusions The combination of theoretical teaching, expert demonstration, and hands‐on training on phantoms proved useful in acquiring skills needed for US‐guided procedures such as SGB and ICB, and can potentially improve graduate and post‐graduate medical education.